The impact of education on the economic growth of Kazakhstan - Baktymbet, A.S.; Baktymbet, S.S.; Serikkyzy, A. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: To examine the factors influencing the development of human capital as the driving force of the economy, identify trends in relations, dynamics, prospects, and results in which human capital affects the economic development of Kazakhstan. Methods: Methods of dialectics, a systematic approach, analysis and synthesis, typology, generalization, concretization, economic and statistical, factor analysis, institutional and cluster analysis. Results: The obtained results show the relationship between human capital and economic growth. Using and the proponent of the endogenous growth model of R. Barro proved that human capital is directly related to economic growth. Human capital is a factor influencing growth, but the degree of impact varies depending on the initial level of accumulated human capital. For example, it is easier for a state with well-developed human capital to adapt future technologies, compared to a state with poor human capital. Conclusions: Based on the results of regression analysis and the criteria of human capital, the following assumptions about the development of human capital are obtained. The knowledge gained from primary and secondary education lags behind, and the overall effect manifests itself after higher education. Higher education is a variable of human capital that affects GDP growth and investments in education, research and development and healthcare are needed, which lead to the accumulation of human capital in the country. Statistics show that primary and secondary education is available to the majority of the population of Kazakhstan. The situation with higher education is different. The acquisition of higher education disappears about 51% of the total population. This means that 49% of the population does not have a higher education. In conclusion, all three types of human capital (education, R&D, and healthcare) are underinvested, which negatively affects the development of human capital in Kazakhstan.
Адами капиталдың дамуына əсер ететін факторлар
Факторы, влияющие на развитие человеческого капитала
Keywords: education system; trends in education; human capital; future education; skills; competencies; labor market